Spatial variations in ambient ultrafine particle concentrations and risk of congenital heart defects. (September 2019) - Lavigne, Eric; Lima, Isac; Hatzopoulou, Marianne; Van Ryswyk, Keith; Decou, Mary Lou; Luo, Wei; van Donkelaar, Aaron; Martin, Randall V.; Chen, Hong; Stieb, David M.; Crighton, Eric; Gasparrini, Antonio; et al.
Abstract: Background: Cardiovascular malformations account for nearly one-third of all congenital anomalies, making these the most common type of birth defects. Little is known regarding the influence of ambient ultrafine particles (<0.1 μm) (UFPs) on their occurrence. Objective: This population-based study examined the association between prenatal exposure to UFPs and congenital heart defects (CHDs). Methods: A total of 158, 743 singleton live births occurring in the City of Toronto, Canada between April 1st 2006 and March 31st 2012 were identified from a birth registry. Associations between exposure to ambient UFPs between the 2nd and 8th week post conception when the foetal heart begins to form and CHDs identified at birth were estimated using random-effects logistic regression models, adjusting for personal- and neighbourhood-level covariates. We also investigated multi-pollutant models accounting for co-exposures to PM2.5, NO2 and O3 . Results: A total of 1468 CHDs were identified. In fully adjusted models, UFP exposures during weeks 2 to 8 of pregnancy were not associated with overall CHDs (Odds Ratio (OR) per interquartile (IQR) increase = 1.02, 95% CI: 0.96–1.08). When investigating subtypes of CHDs, UFP exposures were associated with ventricular septal defects (Odds Ratio (OR) per interquartile (IQR) increase = 1.13, 95% CI: 1.03–1.33), but not with atrial septal defect (Odds Ratio (OR) per interquartile (IQR) increase = 0.89, 95% CI: 0.74–1.06). Conclusion: This is the first study to evaluate the association between prenatal exposure to UFPs and the risk of CHDs. UFP exposures during a critical period of embryogenesis were associated with an increased risk of ventricular septal defect. Highlights: Ambient air pollution in pregnancy increases the risk of congenital heart defects. UFP exposures were not associated with overall congenital heart defects. UFP exposures were associated with risk of ventricular septal defect.